Identifikasi Flashing Pada Mold Alat Cukur - Benny Haddli Irawan; Mufti Fathonah Muvariz; Nicolanta Hiskia Sembiring; Nur Fitria Pujo Leksonowati; Rahman Hakim; Ihsan Saputra (Politeknik Negeri Batam, 2023)
Molding is a process utilized by industries to shape plastic products. One of the plastic molding processes involves injection molding. Injection molding is a procedure where plastic pellets are placed into a hopper or channel and subsequently fed into a barrel. The injection is propelled by a screw mechanism through a machine nozzle and a sprue bushing enters the mold cavity. All of this occurs within a closed mold. A flashing defect in a product refers to an excess material flaw located at the product's edges. To identify the causes of flashing defects in shaving tools, a fishbone diagram is employed, categorizing factors into five: machine factors, material factors, method factors, human factors, and mold factors. The identification results show that flashing defects in shaving tools are primarily attributed to mold factors, where 37 cavities exhibit flashing defects.